Aplikasi Korelasi Kanonikal Pada Faktor – Faktor Yang Mempengaruhi Angka Kematian Ibu Dan Bayi Di Provinsi Jawa Timur - Endang Yuswatiningsih (Akademi Keperawatan Dharma Husada Kediri, 2015)
The purpose of this study was to analyze the relationship between maternal and infant mortality by influenced factors and the factors most closely associated with maternal and infant mortality rates in the province of East Java in 2012. This research uses canonical correlation method that aims to determine the relationship between two variables and identify the dimensions between two groups of variables. The results showed that the variable factors that affect maternal mortality and infant mortality has a strong positive correlation to variable maternal mortality and infant mortality rate. Highest impact of the independent variables for maternal mortality is pregnancy, postpartum maternal, neonatal visits, visiting the baby and toddler care was the infant mortality rate is the delivery by the shaman, neonatal visits and infant visits. Keywords : canonical correlation, maternal mortality rates, infant mortality rates.